Biomass photo-thermal interface evaporation material based on nano TiO2-CNT photocatalytic thermal insulation layer, preparation method and application
By preparing nano-TiO2-CNT photocatalytic insulation layer on cactus flesh, the problem of poor heat concentration of carbon-based biomass materials is solved, and efficient water evaporation and salt resistance are achieved. It is suitable for seawater desalination and sewage treatment, reducing the Production cost.
Patent Information
- Application Number
- CN202411430759.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The heat of existing carbon-based biomass materials cannot be concentrated in the liquid-gas interface during the desalination of solar seawater, resulting in low evaporation efficiency, complex production process, high cost, and low evaporation rate in high concentrations of brine and industrial wastewater.
Using biomass photothermal interface evaporation materials based on nano-TiO2-CNT photocatalytic insulation layer, the water supply layer-insulating layer-photothermal insulation coating and polymerization reaction is designed. The layered structure improves heat concentration and evaporation efficiency.
It achieves an efficient water evaporation rate, improves evaporation efficiency and salt resistance, reduces production costs, is suitable for the evaporation of pure water and high-concentration brine, and has photocatalytic functions, which can handle contaminated water.
Smart Images

Figure BDA0005083605710000061 
Figure HDA0005083605720000011 
Figure HDA0005083605720000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photothermal interface evaporation material preparation, and in particular to a biomass photothermal interface evaporation material based on a nano TiO2-CNT photocatalytic heat-insulating layer, and a preparation method and application thereof. Background Art
[0002] Due to the scarcity of fresh water resources, seawater desalination has become a key source of fresh water supplementation, and many technologies related to seawater desalination have been developed. Among these well-developed technologies, solar-driven seawater desalination technology has attracted the attention of many scholars due to its relatively simple structure, low cost and high desalination efficiency. In a typical solar-driven seawater desalination process, water is injected into the solar evaporator by the capillary action of the evaporator holes.
[0003] At the same time, solar energy is captured by the interface and converted into heat energy through the light absorber, acting as an energy source for the conversion of liquid and gas states. Finally, fresh water is obtained through the condensation step. The performance of the evaporator in the process of seawater desalination is directly related to the speed of seawater desalination and the quality of fresh water finally produced. Therefore, it is extremely important to develop an efficient solar evaporator.
[0004] After a long evolutionary process, natural plants have developed inherent characteristics that make them suitable as materials for the development of high-performance solar evaporators. These characteristics include multi-channel transport structures, excellent hydrophilicity, and a wide range of solar absorption after carbonization. In addition, plants have the advantages of diversity, easy access, affordability, renewability, and eco-friendliness. In recent years, many plant-based biochar solar evaporators have emerged. Because of water pollution, solar desalination based on natural materials faces greater challenges. Evaporating, condensing and collecting water vapor in sewage or seawater to purify water is one of the effective ways to solve the crisis of water pollution and water shortage. However, most of the current carbon-based biomass materials are directly carbonized or only undergo some simple photothermal modification on the surface of the water supply layer, which will cause the heat to be unable to concentrate at the liquid-gas interface, resulting in heat loss, which in turn affects the evaporation effect.
[0005] For example, Zongxing Liu et al. (2024) reported the carbonization technology of winter melon and disclosed Ti3C2T derived from winter melon. X / carbon aerogel, which exhibits excellent photothermal conversion performance for solar steam generation (Ti3C2T X / carbon aerogels derived from wintermelon for high-efficiency photothermal conversion, Desalination, Volume 573, 15 March 2024, 117207). A Chinese patent (Announcement No. CN113968994B) discloses a method for preparing photothermal biomass aerogels for solar interface evaporation using natural porous cellulose biomass materials (such as eggplant, loofah, sugarcane, radish, yam, bamboo and straw). The obtained photothermal biomass aerogels for solar interface evaporation have excellent photothermal properties and can continuously and efficiently convert aqueous solutions into water vapor under the irradiation of sunlight. They can be used as photothermal interface evaporation materials for seawater desalination and wastewater purification. Although the biomass-integrated solar steam generation system has shown a significant technological leap, it still faces the problems of cumbersome production process, low evaporation efficiency, difficulty in obtaining raw materials, seasonal restrictions, low evaporation rate in high-concentration salt water and industrial wastewater, and most of the current carbon-based biomass materials are directly carbonized or only undergo some simple photothermal modification on the surface of the water supply layer, which will cause heat to be unable to concentrate at the liquid-gas interface, resulting in heat loss, which in turn affects the evaporation effect. These factors constitute obstacles that cannot be ignored. Therefore, it is urgent to develop a new type of solar interface evaporation material, whose characteristics should include a simple preparation process, excellent photothermal conversion efficiency, and economical production cost. Summary of the invention
[0006] The purpose of the present invention is to solve the above problems and provide a biomass photothermal interface evaporation material based on a nano TiO2-CNT photocatalytic insulation layer, a preparation method and application thereof.
[0007] In order to achieve its purpose, the present invention adopts the following technical solution:
[0008] A method for preparing a biomass photothermal interface evaporation material based on a nano TiO2-CNT photocatalytic heat-insulating layer comprises the following steps:
[0009] S1. Pulp pretreatment: peel the fresh cactus, cut the pulp into blocks, put it into water, and heat it at 50-70°C under stirring to soften the pulp and remove sugars and impurities;
[0010] S2, preparing a carbonized layer: taking the block of cactus pulp obtained after the treatment in step S1 out of the water and placing it on a heating plate so that one plane of the block of cactus pulp contacts the high-temperature heating plate until the treated surface becomes a black carbonized layer;
[0011] S3. Applying photocatalytic heat insulation coating:
[0012] S3.1. Prepare a photocatalytic heat-insulating coating solution: add nano-titanium dioxide, carbon nanotubes, polyvinyl alcohol, and sodium dodecyl sulfate into water, stir until fully dissolved and mixed evenly, and obtain a photocatalytic heat-insulating layer solution; the mass ratio of nano-titanium dioxide, carbon nanotubes, polyvinyl alcohol, sodium dodecyl sulfate, and water is: 0.02-0.08:0.15-0.35:0.05-0.3:0.06-0.08:25;
[0013] S3.2, coating a photocatalytic heat-insulating coating: taking the prepared photocatalytic heat-insulating coating solution and evenly coating it on the carbonized layer of the cactus pulp block, drying it, and then repeatedly coating the photocatalytic heat-insulating coating solution once, and drying it; preferably, the drying is oven drying;
[0014] S4, coating with pyrrole: take the cactus pulp block treated in step S3.2, and evenly coat the pyrrole on the carbonized layer of the cactus pulp block, and then evenly coat the oxidant aqueous solution with a concentration of 50-80mM on the carbonized layer coated with pyrrole, and fully polymerize to obtain the biomass photothermal interface evaporation material--Ppy / CTPS@cactus.
[0015] The oxidant is selected from one or more of ammonium persulfate, Fe2(SO4)3, and FeCl3; the concentration of the oxidant solution is 55-65mM.
[0016] The stirring speed of the stirring bar under the stirring condition in step S1 is 500-700 r / min, and the heating time under the stirring condition is 32-40 hours; the water is changed every 3-6 hours.
[0017] In step S2, the cactus pulp is heated on a flat plate at a temperature of 300-500° C. until the thickness of the carbonized layer reaches 0.8-1.2 mm; preferably, the flat plate is a metal plate, and the heating time is 3-5 min.
[0018] Preferably, in step S3.1, nano titanium dioxide, carbon nanotubes, polyvinyl alcohol, and sodium dodecyl sulfate are added to water and stirred at 30 to 50° C. for 40 to 120 minutes; the mass ratio of nano titanium dioxide, carbon nanotubes, polyvinyl alcohol, sodium dodecyl sulfate, and water is: 0.02 to 0.05: 0.15 to 0.25: 0.05 to 0.13: 0.06 to 0.08: 25 or 0.05 to 0.08: 0.25 to 0.35: 0.13 to 0.3: 0.06 to 0.08: 25;
[0019] Further preferably, the mass ratio of nano-titanium dioxide, carbon nanotubes, polyvinyl alcohol, sodium dodecyl sulfate and water in the photocatalytic insulation layer solution is: 0.02-0.05: 0.2-0.3: 0.1-0.2: 0.06-0.08: 25 or 0.02-0.05: 0.22-0.27: 0.10-0.15: 0.06-0.08: 25 or 0.02-0.05: 0.25: 0.13: 0.07: 25;
[0020] In step S3.2, each time the photocatalytic heat-insulating coating is applied, 40 to 60 microliters of the photocatalytic heat-insulating coating solution is used for coating per square centimeter of the carbonized layer; the drying is performed in an oven at 55 to 65°C for 3 to 8 minutes.
[0021] In step S4, 40 to 60 microliters of pyrrole are used for coating per square centimeter of carbonized layer, and then 40 to 60 microliters of oxidant aqueous solution are used for coating per square centimeter of carbonized layer;
[0022] The polymerization reaction time is 0.5 to 2 hours, preferably 0.7 to 1.3 hours.
[0023] The block-shaped cactus pulp is in the shape of a cuboid, a cylinder, a prism, a cone or other polyhedrons.
[0024] The block of cactus pulp is in the shape of a cuboid, and its length, width and height are arranged according to the following proportions: length 0.5-1.5 cm, width 0.5-1.5 cm, height 1-3 cm.
[0025] The second aspect of the present invention provides a biomass photothermal interface evaporation material based on a nano TiO2-CNT photocatalytic heat-insulating layer, which is prepared by any of the preparation methods described above.
[0026] The third aspect of the present invention provides the application of the above-mentioned biomass photothermal interface evaporation material based on nano TiO2-CNT photocatalytic insulation layer in solar-driven interface evaporation, photothermal seawater desalination, and sewage treatment.
[0027] The beneficial effects of the present invention are as follows: the Ppy / CPTS@cactus of the present invention adopts a hierarchical material design, a water supply layer (cactus pulp) - insulation layer (CPTS layer) - photothermal layer (polypyrrole) layered structure design, so that more heat is concentrated at the liquid-gas interface, thereby achieving efficient interfacial water evaporation and excellent salt resistance, acid and alkali resistance and photocatalytic performance.
[0028] 1. The present invention has developed a new type of multifunctional biomass interface evaporation material with low cost. Currently, there is no research on using cactus pulp as an interface evaporation material for seawater desalination, and its interface evaporation rate is higher than the evaporation rate of currently reported biomass materials (such as winter melon, eggplant, etc.). By adding a layer of CPTS solution between the photothermal layer and the water supply layer, the heat loss problem of most carbon-based biomass interface evaporation materials is solved, thereby further improving the evaporation rate and evaporation efficiency of the material. Under the irradiation of one sun, its interface evaporation rate in pure water can reach 3.9kg / m 2 / h.
[0029] 2. The present invention uses cactus without seasonal restrictions, low cost, and the preparation process only requires simple water bath heating and top surface carbonization treatment to obtain the substrate, without the need for complex and energy-consuming operation steps such as freeze drying, and can achieve large-scale batch production. Cactus is green, non-toxic, and environmentally friendly. There is no problem of water pollution when it is used as an interface evaporation material.
[0030] 3. The CPTS layer developed by the present invention has both photocatalytic and heat-insulating effects, wherein titanium dioxide not only has heat-insulating properties, but also has good photocatalytic effects, which enables the Ppy / CPTS@cactus of the present invention to also treat polluted seawater, dye wastewater and industrial wastewater, and realize multi-purpose functions. For example, methylene blue and methyl orange are both typical azo dyes, and titanium dioxide can catalytically degrade methylene blue and methyl orange. The carbon nanotubes in the CPTS solution have good photothermal conversion performance and certain heat-insulating functions; polyvinyl alcohol has good heat-insulating properties; sodium dodecyl sulfate as a surfactant can increase the solubility of poorly soluble titanium dioxide and carbon nanotubes in the solution, so that the titanium dioxide and carbon nanotubes in the solution can give full play to their respective functions, and finally make the CPTS layer have good photocatalytic and heat-insulating functions.
[0031] 4. The Ppy / CPTS@cactus of the present invention has good salt resistance, acid and alkali resistance and photocatalytic performance, and also shows a relatively good water evaporation rate in high-concentration salt water, strong acid and strong alkali industrial wastewater and dye wastewater. It also shows a good water evaporation rate in high-concentration salt water. Under the irradiation of one sun, its interface evaporation rate in water with a salt concentration of 25wt% can reach 2.54kg / m 2 / h, thus it solves the shortcoming of low evaporation rate of traditional interface evaporation materials in high-concentration brine.
[0032] 5. Compared with directly carbonizing the cactus pulp to obtain photothermal properties, the present invention uses a simple chemical polymerization method to grow polypyrrole on the top of the cactus pulp, which not only avoids a large amount of energy consumption, but also retains the hydrophilicity of the cactus pulp itself, with high evaporation efficiency, mild conditions and strong operability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 These are actual pictures of the product obtained in Example 1 immersed in water: a. immersed in water with pH=1; b. immersed in water with pH=14.
[0034] Figure 2 The products obtained in Examples 1-7 and Comparative Example 1 were exposed to sunlight (1000W / m 2 ) Curve of the change of water mass in the beaker over time under irradiation.
[0035] Figure 3 The water evaporation rate of the product prepared in Example 1 in real seawater and different salt concentrations.
[0036] Figure 4 This is a scanning electron microscope image of the water supply layer portion of the product obtained in Example 1.
[0037] Figure 5 This is a graph showing the light absorption changes of the products prepared in Examples 1, 4, and 5 in a 10 mg / L methylene blue solution.
[0038] Figure 6 This is a graph showing the changes in light absorption of the products prepared in Examples 1, 4, and 5 in a 10 mg / L methyl orange solution.
[0039] Figure 7 This is a graph showing the photothermal heating performance test results of the product prepared in Example 1. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.
[0041] The experimental methods in the following examples are conventional methods unless otherwise specified.
[0042] Main reagents:
[0043] Nano titanium dioxide: CAS registration number 13463-67-7, particle size 20 nm; commercially available;
[0044] Carbon nanotube (CNT): CAS registration number 308068-56-7; commercially available;
[0045] Polyvinyl alcohol: CAS registration number 9002-89-5; commercially available;
[0046] Sodium dodecyl sulfate: CAS registration number 151-21-3; commercially available;
[0047] Pyrrole: CAS registration number 109-97-7; purity 99%; commercially available.
[0048] Embodiment 1:
[0049] To prepare biomass photothermal interface evaporation materials, follow the steps below:
[0050] 1. Peel the fresh cactus, cut it into pieces (1cm*1cm*2cm), put it into ultrapure water, and then put it into a heat-collecting constant temperature magnetic heating stirrer (DF-101S. Shanghai Lichen Bangxi Instrument Technology Co., Ltd.) for heating and stirring (temperature: 65℃, speed: 600r / min) for 36h, and change the water every four hours.
[0051] 2. Place the pulp obtained after heating and stirring in step 1 in a culture dish, wipe off excess moisture on the surface with absorbent paper, and then place it on an iron plate at a temperature of about 400°C and heat for 3-5 minutes until the treated surface part is completely turned into a black carbonized layer with a thickness of about 1 mm.
[0052] 3. Preparation of photocatalytic thermal insulation coating solution: Add 0.05g of nano-titanium dioxide particles, carbon nanotubes (0.25g), polyvinyl alcohol (0.13g), and sodium dodecyl sulfate (0.07g) into deionized water (25ml), and stir magnetically at 40°C for 1h (speed: 600r / min) to obtain a photocatalytic thermal insulation solution, recorded as CTPS.
[0053] 4. Take 40 μl of the CTPS solution prepared in step 3 and apply it evenly to the carbonized layer surface of the cactus pulp (surface area 1 cm 2 ), then put it into a 60°C oven to dry for 5 min, and then coat it with CTPS solution for the second time, put it into a 60°C oven to dry for 5 min, and then CTPS@cactus can be obtained.
[0054] 5. Use a pipette to apply 40 μL of 99% pure pyrrole on the surface of CTPS@Cactus, then take 40 μL of the prepared 60 mM ammonium persulfate solution and evenly apply it on the surface of CTPS@Cactus with pyrrole added. Polymerize for 1 hour to obtain Ppy / CTPS@Cactus.
[0055] According to the same method as in Example 1, Ppy / CTPS@cactus of Examples 2 to 7 and Comparative Example 1 were prepared. The difference between Examples 1 to 7 and Comparative Example 1 is that the raw material ratios in the photocatalytic heat insulation solution (CTPS) are different. The experimental parameters are shown in Table 1:
[0056] Table 1 CTPS solution ratio
[0057]
[0058] Performance Testing:
[0059] 1. Acid and alkali resistance test
[0060] The product prepared in Example 1 was immersed in strong acid (pH=1) and strong base (pH=14) water for 24 hours, and both were able to maintain a stable form (such as Figure 1 This indicates that the product has good stability and will not be easily damaged by acid or alkali liquids.
[0061] 2. Comparison of water evaporation test
[0062] The prepared product was placed in a beaker containing 100 ml of water and irradiated with a xenon lamp (Cel-S500) equipped with an AM 1.5 filter to simulate sunlight. At the same time, a solar meter (SM206-Solar) was used to calibrate the sunlight intensity to maintain at one sun (1000 W / m 2 ), an electronic balance (AX224ZH / E) records the mass loss of water in the beaker to measure the interfacial evaporation capacity of the sample. Another beaker is filled with 100 ml of water and placed on the balance. The natural evaporation of the system after 1 hour is recorded in a dark field environment as a control group to calculate its actual evaporation efficiency.
[0063] The products obtained in Examples 1 to 7 and Comparative Example 1 were subjected to water evaporation tests. The results of the changes in the mass of water in the beakers of different samples with the solar irradiation time under one sunlight are as follows: Figure 2 The results of water evaporation rate are shown in Table 1. Under the condition of sunlight irradiation, the water mass in the beaker of pure water and different samples changes with the increase of irradiation time. Among them, the water evaporation rate and efficiency of the product prepared in Example 1 can reach 3.87kg / m 2 / h and 92.07%, proving that the Ppy / CPTS@cactus of the present invention has excellent water evaporation effect.
[0064] Comparative Example 1 is different from Example 1 in that the surfactant sodium dodecyl sulfate is not introduced. The results show that its evaporation efficiency in pure water is only 2.28 kg / m 2 / h.
[0065] 3. Salt resistance test
[0066] In order to study the effect of aqueous solutions with different salt concentrations on the evaporation performance of Ppy / CPTS@cactus, deionized water and sodium chloride were used to prepare sodium chloride aqueous solutions with mass fractions of 5wt%, 10wt%, 15wt%, 20wt%, and 25wt%, respectively, and water evaporation experiments were carried out with the product prepared in Example 1. In this study, seawater from Beihai Sea in Guangxi Zhuang Autonomous Region was collected for water evaporation experiments with the product prepared in Example 1, and the average salinity of the seawater was about 3.5wt%.
[0067] from Figure 3 It can be seen that the water evaporation rate of the product prepared in Example 1 in real seawater is still as high as
[0068] 3.02kg / m 2 / h, and in 25wt% salt water, it also showed 2.11kg / m 2 / h, which reflects the excellent salt tolerance of Ppy / CPTS@cactus.
[0069] The evaporation rate is given by the formula It is concluded that (Δm (kg) represents the mass change of the evaporation system, t (h) represents the evaporation time, S (m 2 ) is the effective evaporation area of the evaporator).
[0070] 4. Analysis of the structure of cactus pulp
[0071] The electron microscope image of the product obtained in Example 1 is as follows Figure 4 As shown, from Figure 4 It can be seen that it is composed of honeycomb layered grooves and three-dimensional macroporous structure formed by criss-crossing mesh fibers. It has extremely strong macroporosity and large specific surface area. Therefore, cactus pulp has extremely strong light absorption and water transmission capabilities.
[0072] 5. Photocatalytic experiment
[0073] First, prepare 10mg / L, 7mg / L, 5mg / L, 3mg / L, and 1mg / L methylene blue solutions and methyl orange solutions, and then use a UV spectrophotometer to measure the absorbance at wavelengths of 664nm (methylene blue) and 464nm (methyl orange), record the data, and then make a fitting curve, such as Figure 5 b and Figure 6 As shown in b, it can be seen that the solution prepared this time has a good standard curve.
[0074] Take a 100 ml beaker, add appropriate amounts of 10 mg / L methylene blue solution and methyl orange solution, and then put the products prepared in Examples 1, 4, and 5 into the beaker respectively. Irradiate under 1 sun for 1 hour, collect the evaporated water with a condenser, collect samples at 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min, and then put them into a UV spectrophotometer to measure the absorbance change.
[0075] from Figure 5 and Figure 6 It can be seen that the photocatalytic effect of the products prepared in Examples 1 and 5 is relatively good, but Figure 2It can be seen that the water evaporation rate of the product of Example 5 is much lower than that of the product prepared in Example 1, but its photocatalytic effect is almost the same as that of the product prepared in Example 1, and although the evaporation rate of the product prepared in Example 4 is higher, its photocatalytic effect is much lower than that of the products prepared in Examples 1 and 5. Therefore, in general, the product prepared in Example 1 has the best comprehensive effect.
[0076] 6. Photothermal heating performance experiment
[0077] Test method: The surface temperature change of the product prepared in Example 1 under sunlight conditions was recorded by a thermal imager (Testo 871, Testo Se&Co.Kgaa).
[0078] from Figure 7 It can be seen that the product produced in Example 1 exhibits a significant temperature stratification effect, that is, in the upper water body of the beaker, that is, the light-thermal interface area, the temperature rises significantly and is concentrated, which shows good thermal energy concentration characteristics. This means that when the same sunlight is absorbed by the photothermal material, more energy can be converted into heat energy, and this heat is concentrated near the interface, which helps to promote the evaporation of water, thereby reducing heat loss and improving evaporation efficiency. Figure 7 The data is given in a sunlight intensity (1000W / m 2 ), the surface temperature of the product of Example 1 quickly rose to 38°C in just 5 minutes, and reached a stable surface temperature of 44°C after 30 minutes, and reached 46°C after 1 hour, which shows that the product prepared in Example 1 has good light-to-heat conversion ability.
Claims
1. A method for preparing a biomass photothermal interface evaporation material based on a nano TiO2-CNT photocatalytic insulation layer, characterized in that: The steps include: S1. Pulp pretreatment: peel the fresh cactus, cut the pulp into blocks, put it into water, and heat it at 50-70°C under stirring to soften the pulp and remove sugars and impurities; S2, preparing a carbonized layer: taking the block of cactus pulp obtained after the treatment in step S1 out of the water and placing it on a heating plate so that one plane of the block of cactus pulp contacts the high-temperature heating plate until the treated surface becomes a black carbonized layer; S3. Applying photocatalytic heat insulation coating: S3.
1. Prepare a photocatalytic heat-insulating coating solution: add nano-titanium dioxide, carbon nanotubes, polyvinyl alcohol, and sodium dodecyl sulfate into water, stir until fully dissolved and mixed evenly, and obtain a photocatalytic heat-insulating layer solution; the mass ratio of nano-titanium dioxide, carbon nanotubes, polyvinyl alcohol, sodium dodecyl sulfate, and water is: 0.02-0.08:0.15-0.35:0.05-0.3:0.06-0.08:25; S3.2, coating a photocatalytic heat-insulating coating: taking the prepared photocatalytic heat-insulating coating solution and evenly coating it on the carbonized layer of the cactus pulp block, drying it, and then repeatedly coating the photocatalytic heat-insulating coating solution once, and drying it; preferably, the drying is oven drying; S4, coating with pyrrole: take the cactus pulp block treated in step S3.2, and evenly coat the pyrrole on the carbonized layer of the cactus pulp block, and then evenly coat the oxidant aqueous solution with a concentration of 50-80mM on the carbonized layer coated with pyrrole, and fully polymerize to obtain the biomass photothermal interface evaporation material--Ppy / CTPS@cactus.
2. The preparation method according to claim 1, characterized in that: The oxidant is selected from one or more of ammonium persulfate, Fe2(SO4)3, and FeCl3; the concentration of the oxidant solution is 55-65mM.
3. The preparation method according to claim 1, characterized in that: The stirring speed of the stirring bar under the stirring condition in step S1 is 500-700 r / min, and the heating time under the stirring condition is 32-40 hours; the water is changed every 3-6 hours.
4. The preparation method according to claim 1, characterized in that: In step S2, the cactus pulp is heated on a flat plate at a temperature of 300-500° C. until the thickness of the carbonized layer reaches 0.8-1.2 mm; preferably, the flat plate is a metal plate, and the heating time is 3-5 min.
5. The preparation method according to claim 1, characterized in that: In step S3.1, nano titanium dioxide, carbon nanotubes, polyvinyl alcohol, and sodium dodecyl sulfate are added to water and stirred at 30-50° C. for 40-120 min; the mass ratio of nano titanium dioxide, carbon nanotubes, polyvinyl alcohol, sodium dodecyl sulfate, and water is: 0.02-0.05: 0.15-0.25: 0.05-0.13: 0.06-0.08: 25 or 0.05-0.08: 0.25-0.35: 0.13-0.3: 0.06-0.08: 25; Preferably, the mass ratio of nano-titanium dioxide, carbon nanotubes, polyvinyl alcohol, sodium dodecyl sulfate and water in the photocatalytic insulation layer solution is: 0.02-0.05: 0.2-0.3: 0.1-0.2: 0.06-0.08: 25 or 0.02-0.05: 0.22-0.27: 0.10-0.15: 0.06-0.08: 25 or 0.02-0.05: 0.25: 0.13: 0.07: 25; In step S3.2, each time the photocatalytic heat-insulating coating is applied, 40 to 60 microliters of the photocatalytic heat-insulating coating solution is used for coating per square centimeter of the carbonized layer; the drying is performed in an oven at 55 to 65°C for 3 to 8 minutes.
6. The preparation method according to claim 1, characterized in that: In step S4, Coating with 40 to 60 microliters of pyrrole per square centimeter of carbonized layer, and then coating with 40 to 60 microliters of oxidant aqueous solution per square centimeter of carbonized layer; The polymerization reaction time is 0.5 to 2 hours, preferably 0.7 to 1.3 hours.
7. The preparation method according to claim 1, characterized in that: The block-shaped cactus pulp is in the shape of a cuboid, a cylinder, a prism, a cone or other polyhedrons.
8. The preparation method according to claim 7, characterized in that: The block of cactus pulp is in the shape of a cuboid, and its length, width and height are arranged according to the following proportions: length 0.5-1.5 cm, width 0.5-1.5 cm, height 1-3 cm.
9. A biomass photothermal interface evaporation material based on a nano TiO2-CNT photocatalytic insulation layer, characterized by: The preparation method is described in any one of claims 1 to 8.
10. Application of the biomass photothermal interface evaporation material based on nano TiO2-CNT photocatalytic insulation layer as claimed in claim 9 in solar-driven interface evaporation, photothermal seawater desalination, and sewage treatment.
Citation Information
Patent Citations
Photothermal biomass aerogels for solar interfacial evaporation and their preparation method
CN113968994B
Sewage treatment material with synergism of photo-thermal evaporation and photocatalysis and preparation method of sewage treatment material
CN115745050A
Biomass-based novel solar water evaporator and preparation method and application thereof
CN117164044A
Carbonized loofah photo-thermal evaporator with city wall structure and preparation method and application of carbonized loofah photo-thermal evaporator
CN117699893A
Farm waste-derived recyclable photothermal evaporator
US20240140826A1
Cited By
Water purification method based on photo-thermal catalysis
CN120172483A
Biomass photo-thermal interface evaporation material based on Cu-Zn-S photo-thermal catalytic layer as well as preparation method and application of biomass photo-thermal interface evaporation material
CN120987411A
Biomass-based solar interface evaporator and preparation method and application thereof
CN122540954A